Adapting Bangla Mini-Mental State Examination (MMSE-B) among Healthy Elderly in Bangladesh (Bangladesh Journal of Neuroscience, 2016)
Background: The aim of our study was to determine whether modified Bangla version (MMSE-B) is as effective as mini mental state examination (MMSE) tool for use in Bangladeshi people.Methods: This descriptive observational study was carried out in Department of Neurology, DMCH from January 2013 to December 2013. A total 200 healthy adults (patient attendants at the clinic) who met the inclusion criteria, were interviewed using a structured questionnaire containing information on age, sex, residence, educational backgrounds and questions set at MMSE English version (MMSE-E) and modified Bangla version for MMSE-B (Figure-1). MMSE and MMSE-B both were applied in 1:1 ration. The literate people were asked whether they are comfortable to answer in English (MMSE-E) or they would like the translated form and we applied the form of MMSE (MMSE-T) according to their wish. But in other group of people the modified Bangla version (MMSE-B) was used irrespective of level of education.Result: The mean age at presentation was 58.1±7.8 and 94% were within 50-70 years of age. Male were more common (80, 66) in both the groups and most of them belonging to rural areas. MMSE-B were mostly employed on people having only primary level of education (up to class five, n=80) or no education (n=2), whereas MMSE-E were employed up on people having a level of education higher than class five (n=96). Every question in each item of cognitive domain correlated well (correlation co-efficient range from 0.801- 0.971) except the 7th (correlation co-efficient 0.418) which had higher mean score for MMSE-B than those of MMSE-E (0.90 versus 0.54). The mean score of MMSEB was greater than the mean score of MMSE-E for most of questions except the 1st question that is related to orientation of time. The mean of total score in MMSE-E and MMSE-B were 24.04 and 24.91 respectively with a correlation co-efficient of 0.940.Conclusion: MMSE-B is adaptable for use in Bangladeshi people irrespective of level of education.Bangladesh Journal of Neuroscience 2016; Vol. 32 (2): 91-97